Spiral Curriculum Model in Islamic Boarding School Fiqh Curriculum Management: Turaath-Based Vertical Continuity Analysis - Zainal Abidin; Ahmad Qusairi; Ikmal Wahyudi; Musleh Harry (Yayasan Adra Karima Hubbi, 2026)
Background. The research into Islamic boarding school (pesantren) curricula has mainly centred on the process of institutional change, whereas the internal workings of fiqh turath have received scant attention from the perspective of the modern theory of curriculum. It is noteworthy that turath may be regarded as a means for realizing the idea of a vertical curriculum because the point has never been considered theoretically before. Purpose. This study aims to analyze the vertical continuity of fiqh learning in pesantren and to examine the extent to which the structure of classical texts reflects the characteristics of a spiral curriculum. Method. A qualitative longitudinal case study was conducted at Darullughah Wadda’wah Islamic Boarding School. Data were collected through curriculum documents, examination archives, classroom observations across three instructional levels, and semi-structured interviews with key stakeholders. The analysis employed qualitative curriculum mapping and cognitive task analysis based on the revised Bloom’s taxonomy. Results. The findings show that core fiqh themes recur systematically across instructional levels, accompanied by progressive argumentative deepening and increasing cognitive complexity. This pattern reflects an implicit spiral structure embedded in the mukhtashar–syarah textual tradition, indicating a consistent form of vertical alignment without formal curriculum engineering. Conclusion. This paper contributes theoretically to the discussion by reinterpreting the idea of a spiral curriculum through a text-based epistemology, where it is shown that coherence in curricula can result from the inherent structures in classical texts. This theory is used to develop the Turath-Based Spiral Curriculum Model, which seeks to integrate traditional Islamic education with modern curricular theory. Due to the limitations of the single case study design, this theory is not a general theory but rather a theoretical proposition.